ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEPESERTAAN PROGRAM JAMINAN KESEHATAN NASIONAL PADA PEKERJA INFORMAL PERKOTAAN - Subkhan, Farid (Sekolah Tinggi Ilmu Ekonomi Dewantara, 2018)
National Health Insurance (JKN) was born as mandated by Law No. 40 of 2004 on National Social Security System (SJSN) and the Law No. 24 of 2011 on National Social Security Agency which appointed PT. Askes (Persero) which is then referred to BPJS Kesehatan, followed by Presidential Decree No. 12 of 2013 and Presidential Decree No. 111 of 2013 which has mandated that all Indonesian citizens must be incorporated in JKN program no later than January 1st, 2019. The main challenge is how to attract uninsured people to participate in JKN program within the targeted timeframe. This study examine the probability of urban informal workers as the main target of uninsured people to participate in JKN program based on ten independent variables that are price stimulus, discounts stimulus, payment period stimulus, precautionary motive, access motive, and financial planning knowledge which includes risk management, saving management, retirement planning, heirs planning, and household cash flow management. The study was conducted through direct interviews in Greater Jakarta to 150 informal workers. The results of the study indicate that discount stimulus, access motive to insurance, practicing cash flow management, and heirs planning have significant impact to the person's interest on JKN program.